The Spirit as creator in Gregory Nazianzen’s Or. 41.14 - Harris, BA (Peeters Publishers, 2021)
Previous discussions of Gregory Nazianzen’s Pneumatology have portrayed Gregory’s sharing Basil’s understanding of the Spirit’s creative role as limited to that of ‘perfecting cause’ (Ayres, 2004; Alfeyev, 2006). This article will challenge this characterisation of Gregory’s Pneumatology by showing that, first, Gregory also holds a broader understanding of the Spirit’s creative activity, viewing the Spirit as co-operating with the Father and the Son in the original creation of all things and, second, Gregory diverges from Basil on this point due to his engagement with other pro-Nicene Pneumatological traditions of which Basil was either unaware or chose not to use when developing his account of the Spirit’s creative function.